L'enseignement supérieur russe après l'éclatement de l'Union soviétique : contraintes, processus et changements institutionnels - Darya Loyola
The aim of this research is to analyze by the systemic approach the development of Russian higher education in the post-Soviet era in its functional, structural and historical dimensions. Facing the heavy constraints in the 1990s, the Russian higher education system generates the feedback and propels the processes that affect the system project for the following decades. First, we bring into focus these processes, and then, we analyze, in relation to their development, the institutional change of Russian higher education in the years 2000-2010.